2022
DOI: 10.3390/ani12223068
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Tau (IFNt) and Interferon-Stimulated Genes (ISGs) Expression in Peripheral Blood Leukocytes and Correlation with Circulating Pregnancy-Associated Glycoproteins (PAGs) during Peri-Implantation and Early Pregnancy in Buffalo Cows

Abstract: The objective of this study was to analyze interferon-stimulated genes (ISGs) and interferon tau (IFNt) gene expression in peripheral blood leukocytes during the peri-implantation period and until 40 days of pregnancy in buffalo cows. Relationships were also examined between the expression of ISGs and IFNt and pregnancy-associated glycoproteins (PAGs) peripheral plasma concentration. Buffalo cows were synchronized and artificially inseminated (d 0). Blood samples were collected on days 0, 18, 28 and 40 after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…This finding is in line with the observations made by Buragohain et al [65] who showed an increase of MX2 gene expression in the peripheral blood of pregnant buffalo cows on days 14 and 28, with a ten-fold and fourteen-fold increase in plasma protein levels, respectively. This trend of MX2 expression was also observed in our previous study [38] in which mRNA ISG expression was either evaluated in PBMCs or PMNs.…”
Section: Genesupporting
confidence: 85%
See 2 more Smart Citations
“…This finding is in line with the observations made by Buragohain et al [65] who showed an increase of MX2 gene expression in the peripheral blood of pregnant buffalo cows on days 14 and 28, with a ten-fold and fourteen-fold increase in plasma protein levels, respectively. This trend of MX2 expression was also observed in our previous study [38] in which mRNA ISG expression was either evaluated in PBMCs or PMNs.…”
Section: Genesupporting
confidence: 85%
“…However, in our recent study [38] significant differences in INFt expression were observed in PBMCs between pregnant and nonpregnant buffaloes on days 28 and 40 after AI. In our opinion, these dissimilarities may be due to differences between the methodology applied in this study and the methodology used in our previous study such as different primer-sequence (Fw: CCATTCTGACCGTGAAGAAGTA-Rev: TCATCTCCACTCTGATGATTTCC, (RefSeq.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Interferon Tau (IFNT) or ovine trophoblast protein-1 oTP-1 is a pregnancy recognition signal in ruminants, secreted by trophectoderm after embryo elongation on day 10 and ceases after day 21 [5][6][7][8]. In addition to its role in pregnancy recognition, IFNT has other functions such as anti-luteolytic and CL protective [9], preventing rejection and supporting progesterone secretion [10].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, novel transcripts such as interleukin 6 ( IFI6), radical S-adenosyl methionine domain containing 2 (RSAD2), interferon induced protein 44 (IFI44), 2′-5′-oligoadenylate synthetase 2 (OAS2 ), galectin 3 binding protein (LGALS3BP), interferon induced transmembrane protein 2 (IFITM2), TNF superfamily member 13B (TNFSF13B), C-type lectin domain family 3 member B (CLEC3B), and dermokine ( DMKN) were expressed in bovine PBMCs during early pregnancy (Rocha et al ., 2020). Other studies showed increased protein expression of myxovirus resistance protein 2 (MX2: Buragohain et al, 2016) and recombinant ISG15 (the product of interferon-stimulated gene 15: Batra et al ., 2018) as well as mRNA expression of ISG15, MX2, 2′-5′-oligoadenylate synthetase 1 ( OAS1 ) and IFNT in PBMC of early pregnant buffalo (Casano et al ., 2022).…”
mentioning
confidence: 99%